A WHO tool for risk‐based decision making on blood safety interventions. Issue 2 (25th December 2020) - Janssen, Mart P.; Nuebling, C. Micha; Lery, François‐Xavier; Maryuningsih, Yuyun S.; Epstein, Jay S.
Abstract: Background: Risk‐based decision making is increasingly recognized as key to support national blood policy makers and blood operators concerning the implementation of safety interventions, especially to address emerging infectious threats and new technology opportunities. There is an urgent need for practical decision support tools, especially for low‐ and middle‐income countries that may not have the financial or technical capability to develop risk models. WHO supported the development of such a tool for blood safety. The tool enables users to perform both a quantitative Multi‐Criteria Decision Assessment and a novel step‐by‐step qualitative assessment. Study Design and Methods: This paper summarizes the content, functionalities, and added value of the new WHO tool. A fictitious case study of a safety intervention to reduce the risk of HIV transmission by transfusion was used to demonstrate the use and usefulness of the tool. Results: Application of the tool highlighted strengths and weaknesses of both the quantitative and qualitative approaches. The quantitative approach facilitates assessment of the robustness of the decision but lacks nuances and interpretability especially when multiple constraints are taken into consideration. Conversely, while unable to provide an assessment of robustness, the step‐by‐step qualitative approach helps structuring the thought process and argumentation for a preferred intervention in a systematic manner. Conclusion: The relative strengths and weaknesses of the quantitative and step‐by‐step qualitative approach to risk‐based decision making are complementary and mutually enhancing. A combination of the two approaches is therefore advisable to support the selection of appropriate blood safety interventions for a particular setting.